2019
DOI: 10.1111/mec.15186
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide variation in DNA methylation is associated with stress resilience and plumage brightness in a wild bird

Abstract: Individuals often differ in their ability to cope with challenging environmental and social conditions. Evidence from model systems suggests that patterns of DNA methylation are associated with variation in coping ability. These associations could arise directly if methylation plays a role in controlling the physiological response to stressors by, among other things, regulating the release of glucocorticoids in response to challenges. Alternatively, the association could arise indirectly if methylation and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
(130 reference statements)
0
37
0
Order By: Relevance
“…Furthermore, in a previous study, the transcriptional repression of DNMT1 by glucocorticoid exposure is considered as a proxy for stress response [105]. Hypermethylation plays a role in controlling the physiological response to stressors by regulating the release of glucocorticoids in response to challenges [106]. Our results indicate that preconditioning with RPM supplementation might produce an activation of the process of DNA methylation during transportation stress.…”
Section: Plos Onementioning
confidence: 66%
“…Furthermore, in a previous study, the transcriptional repression of DNMT1 by glucocorticoid exposure is considered as a proxy for stress response [105]. Hypermethylation plays a role in controlling the physiological response to stressors by regulating the release of glucocorticoids in response to challenges [106]. Our results indicate that preconditioning with RPM supplementation might produce an activation of the process of DNA methylation during transportation stress.…”
Section: Plos Onementioning
confidence: 66%
“…While some studies have found genomic signatures of urban adaptation (Harris et al., 2013; Salmón et al., 2020) and consistent differences at the transcriptomic level (Watson et al., 2017), others have found no genetic structure among urban and nonurban congeners (Khimoun et al., 2020). Modifications in DNA methylation have been shown to associate with anthropogenic‐linked factors including feeding on anthropogenic‐provided food in baboons (Lea et al., 2016), exposure to pollution in humans (Baccarelli et al., 2009), and stress resilience in response to handling in tree swallows (Taff et al., 2019). A few studies have specifically investigated epigenetic variation in wild animals in the context of urbanization, revealing varied patterns (Garcia et al., 2019; McNew et al., 2017; Riyahi et al., 2015; Thorson et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additional techniques can further be incorporated to identify the function of the methylated restriction sites in question. For example, methylated regions of the genome were associated with plumage and physiological traits in female Tree Swallows Tachycineta bicolor , where individuals with brighter breast plumage and higher stress resilience had lower methylation (Taff et al 2019). Similarly, a future study could determine whether the statistically significant restriction sites in our study are related to traits that allow females to have a higher BCI (Latta et al 2016) or influence their fitness when shale gas disturbed areas affected reproductive success and productivity (Frantz et al 2018a).…”
Section: Discussionmentioning
confidence: 99%